Díaz Solimine, Omar L. (dir.); Díaz Solimine, Ignacio L. (coord.), El margen nacional de apreciación, Ciudad Autónoma de Buenos Aires, Astrea, 2020, 328 pp - Ratti Mendaña, Florencia Soledad (2022)
Fil: Ratti Mendaña, Florencia Soledad. Pontificia Universidad Católica Argentina. Facultad de Derecho; Argentina